Biobased thermosetting cellular blends: Exploiting the ecological advantage of epoxidized soybean oil in structural foams - Agnihotri S.; Shukla S.; Pradeep S.A.; Pilla S. (My University, 2025)
In this study, the effect of epoxidized soybean oil (ESO) on the thermomechanical properties of foams based on epoxidized pine oil (EPO) was investigated. To obtain homogeneity in microstructure, an in-house developed, delayed addition approach was adopted for foaming compositions with polymethylhydrosiloxane (PMHS) while varying ESO content from 10% to 50%. The resulting foams were characterized with respect to microstructure, mechanical and thermal properties. The influence of rheology of blend compositions before gelation on the cell morphology was examined and a prospective approach was proposed for optimality in cell size. Although pure ESO did not cure at room temperature, blending with EPO facilitated processing the foams at room temperature, thereby curtailing the overall energy input in commercially manufacturing such composite systems. The behavior of foams under compressive loading was studied, and the compressive strength was observed to exhibit a decrease from 5.24 to 1.13 MPa with increase in ESO content. The nature of collapse plateau however suggested an increase in the fraction of load supported by the fluid in this region. This juxtaposed with a decrease in foam density deviated from Rehkopf's evaluation of load distribution between polymer and fluid. The foams were shown to exhibit high thermal stability, which increased from 182 to 208 °C with the amount of ESO present in the matrix. © 2019 Elsevier Ltd